Model Konseptual untuk Mengintegrasikan Realitas Campuran dan Kecerdasan Buatan dalam Aplikasi Warisan Budaya - Alifeony Mutiara Diarsya; Ari Widyanti; Tara Taufiqur Rahman (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2026)
This study conducts a systematic literature review (SLR) to justify the integration of Mixed Reality (MR) and Artificial Intelligence (AI) in cultural heritage applications, aiming to enhance user engagement through a conceptual model. The review identifies four key dimensions namely, immersion, adaptivity/personalization, embodiment, and interactivity, as critical factors influencing presence and engagement. Through the synthesis of 21 studies, the proposed conceptual model demonstrates how embodiment, immersion, interactivity, adaptive and personalization collectively strengthen user presence and engagement. Immersion establishes the psychological foundation for presence, reinforced by dynamic AI-driven content and contextualized experiences. Adaptivity and personalization enable systems to respond to user preferences, fostering repeated interaction and experience sharing. Embodiment, through body ownership and perspective-taking, transforms users into active narrative agents, deepening emotional and cognitive involvement. Interactivity, supported by multimodal inputs and gesture-based controls, acts as a direct driver of engagement by enabling responsive and participatory storytelling. Collectively, this conceptual model provides demonstrate that AI-MR integration strengthens the presence and engagement relationship for cultural heritage preservation, interpretation, and public participation.